Growth Effect of Foreign Direct Investment in Asean Economies: Does Institutional Quality Matter? - Nguyen, Bao-Chau Xuan; Ho, Thị Lam (Organizations and Markets in Emerging Economies, 2025)
This paper empirically studies how foreign direct investment affects economic growth and how this effect depends on institutional quality. Using threshold regression analysis on panel data for nine ASEAN countries from 2002 to 2020, the estimated results indicate a nonlinear impact of foreign direct investment on growth across various institutional regimes. When the institutional quality falls below the threshold value, foreign direct investment has a negative effect on growth. However, when institutional quality exceeds this value, foreign direct investment contributes positively to economic growth. In particular, we observe that FDI facilitates economic growth in most ASEAN countries when institutional quality is above the threshold value, except for Laos. This finding emphasizes that institutional quality significantly influences the effectiveness of foreign direct investment on economic growth. Based on the research findings, we propose several policy implications to improve institutional quality in ASEAN countries to enhance the positive impact of foreign direct investment on the economy.